2018
DOI: 10.15275/rusomj.2018.0402
|View full text |Cite
|
Sign up to set email alerts
|

The apoptotic activity of flavonoid-containing Gratiola officinalis extract in cell cultures of human kidney cancer

Abstract: Objective -The discovery of the apoptosis-inducing effects of flavonoid vagonin allowed to make an assumption of existence of similar effect in others flavonoids. This study is devoted to the effects of Gratīola officinālis extract on cell culture of the human kidney cancer.Methods -Cell cultures of human kidney carcinoma -Caki-1 and SN12c were used in the study. The cells were stained with Hoechat 33258 dye. The number of living cells, cells in a state of apoptosis and mitosis were counted. The Cramer-Welch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…In the present study, the expression of caspase-3 in the diabetic group was significantly greater than that of the control, which is in conformity with this result that caspase-3 is expressed through apoptosis (49). The same amount of caspase-3 gene expression in the D+L group was correlated with an investigation indicating the considerable role of flavonoids in the apoptosis of the kidney (47). As reported earlier, flavonoids probably stimulate apoptosis through the development of caspases-3, -8, and -9 in the cellular pathway (50,51).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the expression of caspase-3 in the diabetic group was significantly greater than that of the control, which is in conformity with this result that caspase-3 is expressed through apoptosis (49). The same amount of caspase-3 gene expression in the D+L group was correlated with an investigation indicating the considerable role of flavonoids in the apoptosis of the kidney (47). As reported earlier, flavonoids probably stimulate apoptosis through the development of caspases-3, -8, and -9 in the cellular pathway (50,51).…”
Section: Discussionsupporting
confidence: 91%
“…It has also been demonstrated that the stimulation of the NF-κB pathway can support apoptosis (43), and NF-κB could persuade the expression of caspase-induced apoptosis (44). The anticancer activities of flavonoids, as we observed in the leaf extracts, have been proven in animal and human kidney models, by inhibiting cell proliferation and inducing apoptosis with varied amounts of IC 50 (45)(46)(47).…”
Section: Discussionmentioning
confidence: 76%
“…Оценка возможностей флуоресцентных методов исследования по сравнению с фазовым контрастом показала, что даже при использовании простого двойного окрашивания акридиновым оранжевым и йодистым пропидием возможно проводить эффективный скрининг новых противоопухолевых препаратов с определением не только цитотоксической, цитостатической активности [21], но и цикла клетки (фазы митоза), количества ядрышек, наличия аутофагосом, пикноза, апоптоза и резистентности опухолевых клеток к лечению из-за развития в них аутофагии. Это было невозможно ранее при отдельном окрашивании одним или несколькими другими флуоресцентными красителями.…”
Section: Discussionunclassified
“…Аутофагия позволяет опухолевым клеткам выживать за счет избавления от поврежденных органелл и получения новых ресурсов для восстановления. Поэтому появление аутофагосом при проведении химиотерапии может являться признаком резистентности опухолевых клеток, хотя на сегодняшний день нет единого мнения о их роли как фактора, способствующего опухолевого росту [21][22][23][24]. В отличие от общепринятого в клеточной биологии одиночного окрашивания флуоресцентным красителем предложенное нами двойное окрашивание в тесте " живые и мертвые" (заявка на изобретение № 2018105465 от 13.02.18) продемонстрировало не только роль аутофагии в развитии резистентности опухолевых клеток, но дало возможность более эффективно проводить скрининг препаратов, способных подавлять такую резистентность.…”
Section: Discussionunclassified
“…With the specific impact on tumor cells and without any impact on normal and nontransformed ones, quercetin has fascinated many researchers to investigate its potential as an adjuvant to suppress oxidative stress, proliferation, and metastasis [78]. Several studies showed the inhibitory impacts of quercetin against pancreatic, colorectal, prostate, lung, ovarian, nasopharyngeal, breast, and kidney cancers [79][80][81][82][83][84][85]. A number of recent clinical studies have scrutinized quercetin's effect on PC.…”
Section: Flavonoids and Anticancer Effects: Key Focus On Quercetinmentioning
confidence: 99%